2006
DOI: 10.1080/14765280600551240
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Scale Efficiencies for Chinese Rural Credit Cooperatives: A Bootstrapping Approach in Data Envelopment Analysis

Abstract: Chinese rural credit cooperatives (RCCs) are a major supplier of credit to the rural sector in the country. However, Chinese RCCs are currently encountering operating problems, and an experimental reform is being carried out to restructure and reform the RCCs. In order to have some idea about the efficacy of reform, it is important to have an understanding of the institutional economics underlying the delivery of rural credit in China. This paper evaluates pure technical efficiency, overall technical efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
2
21
0
2
Order By: Relevance
“…Because of high operational costs (such as those related to screening, monitoring, and enforcement), high financial risk (such as risks due to moral hazard, few assets for collateral [2], and client's income stability), and low returns (because of interest ceilings set by the government) (Dong and Featherstone, 2006), formal financial institutions have strict requirements for rural loans and limited lending.…”
Section: Formal Credit Marketsmentioning
confidence: 99%
“…Because of high operational costs (such as those related to screening, monitoring, and enforcement), high financial risk (such as risks due to moral hazard, few assets for collateral [2], and client's income stability), and low returns (because of interest ceilings set by the government) (Dong and Featherstone, 2006), formal financial institutions have strict requirements for rural loans and limited lending.…”
Section: Formal Credit Marketsmentioning
confidence: 99%
“…Much prior research has found that Chinese rural households suffer from a lack of access to credit (International Fund for Agricultural Development 2001;Luo 2004;Dong and Featherstone 2006;Yu 2008).…”
Section: Credit C O N S T R a I N T S A N D P E N S I O N I N Ruramentioning
confidence: 99%
“…Dong and Featherstone (2004) suggest further improving the smoothed bootstrap D ** o; j to obtain e D ** o; j , which has an asymptotically correct variance. This is done in the following way…”
Section: Malmquist Productivity Indexmentioning
confidence: 97%